Implementing media educational technology in Ukrainian preschool institutions - Volodymyr M. Chaika; Iryna I. Kuzma; Oleksandra I. Yankovych; Kateryna M. Binytska; Oksana T. Pysarchuk; Tetiana V. Ivanova (Academy of Cognitive and Natural Sciences, 2024)
This study investigates the implementation of media educational technology in preschool institutions in Ukraine. The increasing prevalence of media manipulation, fake information, and uncontrolled media consumption among children necessitates media education from an early age. The research involved developing and experimentally testing a model for media educational technology tailored for preschoolers aged 5-6 years. The technology encompasses a three-stage process: diagnostic-target, integrational, and analytical, incorporating various forms, methods, and means of media education activities. A key component is innovative "media educational tales" designed to engage children in learning about media literacy concepts. The effectiveness of the technology was evaluated through a confirmatory experiment conducted in multiple preschool institutions across Ukraine, involving 384 respondents. The results demonstrated a significant improvement in media literacy levels among children in the experimental groups, with 20.9% achieving a high level and 61.7% reaching a sufficient level after implementing the technology. The study highlights the feasibility and positive impact of implementing structured media educational approaches in preschool settings while also revealing the need for further training and support for preschool teachers in this domain.